An FORMAL EDUCATION FOR WOMEN ENABLEMENT: An assessment of how formal education assist women to be enabled in Chirumanzu district - CHIMBINDI, TAKAWIRA (Advances in Social Sciences Research Journal, 2021)
Universally, there is concern for women enablement and United Nations Educational Science and Cultural Organisational (UNESCO) cites Zimbabwe as having 17% of the adult population being illiterate with two thirds being women (Kadada, 2014). Despite efforts by the government of Zimbabwe through formal education and other key players such as Non-governmental Organizations (NGOs) in ensuring women enablement, women have not been fully integrated into many development spheres. As alluded by Pietila, and Vickers, (1996), that the subordinate position of women limits their ability to effectively indulge in development activities and women in Chirumanzu district are no exception. They continue to be seen as a missing link in being effective stakeholders in development processes. A notable pattern inherently evident on the ground is that few women are socially, politically, and economically active in development programmes. Hence the need to advocate for women enablement through formal education. According to Pietila, and Vickers, (1996), “empowerment is an active, multidimensional process which enables women to realize their full identity and power in all spheres of life”. Women in Chirumanzu district need to be enabled enough to know their rights, to have access to knowledge and resources, greater autonomy in decision making, greater ability to plan their lives, greater control over the circumstances that influence their lives and finally to be free from customs, beliefs that are barriers to their enablement. In light of the above, this study therefore endeavours to assess how formal education has assisted women in Chirumanzu district to be enabled.